The importance of HIV screening in a sexual trasnmitted disease (STD) outratient department - Pereira, Judite; Godinho, Mário; Barata, A. Feio (Brazilian Journal of Sexually Transmitted Diseases, 1998)
It is well established the importance of the HIV screening in the group of parients regulary observed in a STD outpatient depanment. The aurhors present a study that reveals a high proportion of posicive HIV screening in a considerable number of parients previously unknown HIV carriers. Some inceresting clinical cases area aso reported.